Unpacking the Phillips Curve in the Mena Region (Excluding High-Income Countries): Trends and Implications for Policy in the Period 1990-2022 - Hassan, Fatma Ahmed (Journal of Ecohumanism, 2024)
The effects of inflation and unemployment are particularly severe in developing and impoverished nations because wealthy nations can afford to compensate their citizens with tax breaks, unemployment benefits, and other benefits, while poor and developing nations are unable to do so. Therefore, this study aimed to ascertain the degree to which the Phillips curve covers the Middle East and North African (MENA) countries and noted that high-income countries were not included in this analysis due to the previously stated reasons. The ARDL model was created to examine the effects of inflation and unemployment on the economic growth rate. Statistics published in the World Bank database during the period 1990–2022 were used. The Granger model’s causal relationship was examined using the E-Views12 program. All findings support the absence of a Phillips curve in those nations, ARDL model results were in line with the Granger causality results. This is in line with the findings of (Tarek Kacemi and Sal-lahuddin Hassan:2018) and (Muhammad Azam, Rasheed Khan, and Saleem Khan:2021). The results also demon-strate a negative relationship between unemployment and GDP growth rates which is consistent with economic theory, between the rate of inflation and economic growth. This finding validates historical labor market distor-tions in these nations and highlights the need for different labor policies that are appropriate for each nation’s circumstances and compatible with economic variables. Meanwhile, those nations can adopt economically con-sistent measures to address inflation, such as raising taxes, cutting back on spending, or adopting other customary measures.